The Weavers of Trautenau: Jewish Female Forced Labor in the Holocaust. Janine P Holc - Baer, Elizabeth R. (Holocaust and genocide studies, 2025)
The eponymous weavers of Trautenau were a group of approximately three thousand Polish Jewish girls and women, ranging from eleven to twenty years old, who